Akademischer Mittelbau 2030 - Die HybridmitarbeiterInnen - Bracher, Birgit; Ziemainz, Heiko (Ze-phir, 2017)
UnivIS-Import:2017-12-18:Pub.2017.phil.dss.lsw.akadem

An Explorative Study of Possible Demographic Variables, Sports-related Situational Variables and Social Variables as Predictors of Athlete Burnout and Its Core Dimensions among German Non-elite Endurance Athletes. - Ziemainz, Heiko; Drescher, Amely; Schipfer, Melanie; Stoll, Oliver (Advances in Physical Education, 2015)
UnivIS-Import:2015-03-09:Pub.2015.phil.dps.iss.lsw.anexpl

Ansätze fächerübergreifenden Latein-/Sportunterrichts - Viehoff, Franziska; Ziemainz, Heiko (Sportunterricht, 2020)

A Quality Assured System of Selecting and Promoting Athletic Talents - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (BISp-Jahrbuch 2003, 2004)
UnivIS-Import:2015-04-20:Pub.2004.phil.dps.iss.lsw.aquali

Bestands- und Bedarfsanalyse als Voraussetzung einer effektiven Sportentwicklungsplanung (SEP) am Beispiel einer sächsischen Kommune - Ziemainz, Jana; Ziemainz, Heiko (Bewegte Kommune - Gesunde Kommune, 2002)
UnivIS-Import:2015-04-20:Pub.2002.phil.dps.iss.lsw.bestan

Bestands- und Bedarfsanalyse sportpsychologischer Betreuung im Raum Nordbayern - Waldenmayer, Denise; Ziemainz, Heiko (Zeitschrift für Sportpsychologie, 2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dps.iss.lsw.bestan

Bewegter Lateinunterricht - Viehoff, Franziska; Ziemainz, Heiko (Lehrhilfen für den Sportunterricht, 2020)

Bewegter Mathematikunterricht - Utz, Katrin; Ziemainz, Heiko (Lehrhilfen für den Sportunterricht, 2021)

Bewegter Sprachunterricht - Viehoff, Franziska; Ziemainz, Heiko (Sportpraxis, 2020)

Burnout as a psychological disorder in competitive athletics - Krippl, Martin; Ziemainz, Heiko (Advances in Psychology Research 69, 2010)
The growing interest in the burnout syndrome in the field of athletic science is a recent phenomenon (Kallus & Kellmann, 2000). The study to be reviewed here involved the long-term use of a questionnaire and altogether 363 competitive athletes, and purports to apply predictive parameters from the transactional model (Lazarus, 1992) and the conservation of resources theory (see, for example, Hobfoll, 2001) in order to predict three dimensions of burnout. We applied the German version of the Athlete Burnout Questionnaire (ABQ, Raedeke & Smith, 2001), which distinguishes three dimensions: “emotional/physical exhaustion” (Burnout-E), “reduced sense of accomplishment” (Burnout-RA) and “sports devaluation” (Burnout-D). Because the three dimensions show clearly different courses of development, they will be analyzed here for the first time individually. For each of the burnout subscales a linear regression was computed with the following group variables: personality factors, motivation (MOMS), environmental factors, resource losses (COR-E-G), resource gains (COR-E-G), stress regulation styles (SVF), and discomfort. Results demonstrate for all the burnout subscales that trait anxiety has the strongest effect and enjoyment has a strong one. An influence from “resource gains” could be seen only for “sports devaluation”. Analysis showed that losses in self-confidence were the only relevant resource loss for the subscale emotional-physical exhaustion.
UnivIS-Import:2017-12-18:Pub.2010.phil.dss.lsw.burnou
Keywords: Burnout; Competitive athletes; Conservation of resources theory

Burnout as a psychological disorder in competitive athletics - Ziemainz, Heiko; Krippl, Martin (Advances in psychology research, 2010)
Keywords: burnout; psychological disorder

Burnout im Sportlehrerberuf - Schneider, Markus; Ziemainz, Heiko (Sportunterricht, 2015)
Burnout ist ein in den letzten Jahren oft gehörter und verwendeter Begriff im Kontext von Überlastung/Überbeanspruchung in der Arbeitswelt. Gerade der Lehrerberuf mit seinen vielfältigen Anforderungen/Stressoren und deren unzureichende Bewälti-gung scheinen die Entstehung eines Burnout-Syndroms zu begünstigen. Gerade der Sportlehrer ist einer Vielzahl von möglichen Stressoren ausgesetzt (u.a. Disziplinlosigkeit der Schüler, Benotungs- und Motivationsprobleme, inadäquate räumliche Gegeben-heiten, hohe physikalische Reize (Lärm und Stimmbelastung, geringeres Ansehen im Kollegium). Es ist jedoch möglich, durch entsprechende individuenzentrierte Maßnahmen und/oder spezielle Programme vorzubeugen.<br
UnivIS-Import:2015-03-09:Pub.2015.phil.dps.iss.lsw.burnou

Burnout im Sport. Zur Prävalenz von Burnout aus bedingungsbezogener Perspektive - Ziemainz, Heiko; Abu-Omar, Karim; Raedeke, Tom; Krause, Katharina (Leistungssport, 2004)
UnivIS-Import:2015-03-09:Pub.2004.phil.dps.iss.lsw.burnou

Burn-out wirksam vorbeugen mit bewegungsbezogenen Interventionen? - Peters, Stefan; Götz, V; Kannegießer, Daniel; Ziemainz, Heiko (Bewegungstherapie und Gesundheitssport, 2014)
Sowohl Beeinträchtigungen der psychischen Gesundheit im Allgemeinen als auch die Zusatzdiagnose Burn-out im Speziellen haben in den letzten Jahren zugenommen bzw. sind öfter diagnostiziert worden. Der präventive Nutzen von bewegungsbezogenen Interventionen im Hinblick auf Burn-out ist bisher unzureichend aufgearbeitet. Hierzu wurde ein narratives Review durchgeführt. Speziell zur Prävention von Burn-out ließen sich lediglich 4 Interventionsstudien identifizieren, von denen nur in einer eine randomisierte Gruppenzuteilung stattgefunden hat. Die Maßnahmen reichen von einem reinen Ausdauertraining über 2 mehrdimensionale Bewegungsprogramme bis hin zum rein selbstgesteuerten, Incentive-gestützten Training. Im Hinblick auf das Outcome Burn-out scheinen bewegungsbezogene Interventionen Effekte zu erzielen, die vergleichbar mit denen kognitiver Interventionen sind. Ein höheres Ausmaß an Bewegung steigert möglicherweise die Wirkung. Die Befunde dieser Übersicht und die Erkenntnisse zu Wirkungen von Bewegung auf Burn-out-nahe Konstrukte verleihen der Notwendigkeit Nachdruck, dass existierende bewegungsbezogene Interventionen verbreitet und evaluiert werden.<br
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.lsw.burnou
Keywords: Burn-out; Prävention; bewegungsbezogene Interventionen

“Character Is the Most Important Thing in Soccer”—A Pilot Study on the Development and Effectiveness of a Character Building Program in High-Performance Youth Soccer - Linder, Stephanie; Jörg, Robert; Ziemainz, Heiko (Advances in Physical Education, 2022)
Background: Strength of character plays an important role in high-performance soccer. Yet little attention is paid to the character development of young athletes in most youth programs. Objective: The purpose of this pilot study was to describe the development of a new character building program and to evaluate its effectiveness on strength of character domains and implicit theories of intelligence and talent in a high-performance youth soccer club in Germany. Methods: A pre-post mixed-methods pilot study was conducted with 42 youth players. The intervention group (n = 14) was compared with a club-internal control group (n = 14) and one control group from an amateur soccer club setting (n = 14). The Implicit Theories of Intelligence Scale was used to measure the player’s incremental beliefs about intelligence and talent and a new designed questionnaire was used to measure the strength of character. The quantitative analysis included Mann-Whitney-U and Wilcoxon tests. For the qualitative analysis, essays of the intervention group were thematically coded. Results: At baseline, the implicit theories of talent scores and the strength of character scores were higher in the intervention group compared with the amateur club players, whereas implicit theories of intelligence scores were non-significant. In the intervention group, scores on implicit theories of intelligence (p = 0.003) and strength of character (p = 0.004) were significantly higher at the end of the program compared with baseline. Conclusions: The character building intervention increased the incremental beliefs about intelligence and the strength of character in the young players of a high performance youth soccer club. These results are an important first contribution regarding the development and integration of character building in the context of professional youth soccer.<br
Keywords: High-Performance Youth Soccer; Strength of Character; Growth Mindset

Corrigendum: “For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women(Front. Public Health, (2022), 10, (867626), 10.3389/fpubh.2022.867626) - Sauter, Alexandra; Herbert-Maul, Annika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Frahsa, Annika; Linder, Stephanie; Herrmann-Johns, Anne (Frontiers in Public Health, 2023)
In the original published article, a data reanalysis is included which relates to a physical activity promotion project that has been running at various sites in Germany since 2005. The qualitative data used for the published reanalysis was collected between 2007 and 2011. A detailed description of the data set used and the reanalysis we conducted can be found in the methods section of the published article. In the published article, Roger, Rutten, Frahsa, Abu- Omar and Morga (2011) was cited three times. The corrigendum now includes further references to the work of Roger et al. (2011) and new to Rutten et al. (2008) in the introduction, method, and discussion sections of our paper.
CRIS-Team Scopus Importer:2023-03-17
Keywords: community-based participatory research; empowerment; ethnic minority; health promotion; low socioeconomic status; physical activity; qualitative research; women's health

Der Einsatz Mentalen Trainings im triathlonspezifischen Disziplinwechsel - Ziemainz, Heiko (Leipziger Sportwissenschaftliche Beiträge, 1999)
UnivIS-Import:2015-03-05:Pub.1999.phil.dps.iss.lsw.derein

Der Einsatz von mentalem Training in der Rehabilitation von Schlaganfallpatienten - Review und Effektstärkenberechnung - Ziemainz, Heiko; Hendrich, Simon Klaus; Schleinkofer, Michael; Pfeifer, Klaus (Diagnostic and interventional imaging, 2007)
UnivIS-Import:2015-04-14:Pub.2007.phil.dps.iss.psbg.derein

Der Einsatz von Mentalem Training in der Rehabilitation von Schlaganfallpatienten - Review und Effektstärkenberechnung - Ziemainz, Heiko; Hendrich, Simon Klaus; Schleinkofer, Michael; Pfeifer, Klaus (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2008)

Der Umgang mit Aggression - Anregungen für den Sportunterricht - Merkel, Simone; Ziemainz, Heiko (Sportpraxis, 2010)

Determinanten der Talententwicklung im internationalen Vergleich. Theoretischer Ansatz und Ergebnisse einer 4-Länder-Studie - Rütten, Alfred; Röger, Ulrike; Ziemainz, Heiko (Sportwissenschaft, 2006)
UnivIS-Import:2015-03-09:Pub.2006.phil.dps.iss.lsw.determ

Die Gefährdung zur Sportsucht in Ausdauersportarten - Ziemainz, Heiko; Stoll, Oliver; Drescher, Amely; Erath, Rafael; Schipfer, Melanie; Zeulner, Bernd (Deutsche Zeitschrift für Sportmedizin, 2013)

Die Messung aktuellen Wohlbefindens im Gesundheitssport - Ziemainz, Heiko; Peters, Stefan (Sportwissenschaft, 2010)
Körperlich-sportlicher Aktivität wird unter bestimmten Voraussetzungen das Potenzial zur positiven Beeinflussung des Wohlbefindens zugeschrieben. Akteure im Gesundheitssport sollten deshalb die Möglichkeit haben, ihr Handeln hinsichtlich seiner Auswirkung auf das Wohlbefinden der Teilnehmer zu überprüfen. Die Absicht dieser Arbeit ist es, einen überblick über existierende Messinstrumente und Empfehlungen für die praktische Anwendung zu geben. Hierfür wurde die Suche auf multidimensionale Fragebögen eingeschränkt, die das aktuelle Wohlbefinden messen. Nachdem in der Einleitung eine Differenzierung des Wohlbefindens vorgenommen und mögliche Mechanismen dargestellt wurden, welche die positiven Effekte körperlich-sportlicher Aktivität erklären, werden 5 Instrumente eingehend betrachtet, z. B. Positive Negative Affect Scale (PANAS), Befindlichkeitsskalen (BFS), Profile of Mood States (POMS). Die Fragebögen variieren beträchtlich hinsichtlich des theoretischen Hintergrunds, der psychometrischen Eigenschaften und des Aufbaus. Die Eignung für unterschiedliche Einsatzgebiete kann daran festgemacht werden. So empfehlen sich z. B. das POMS hinsichtlich der internationalen Vergleichbarkeit, die PANAS durch den ökonomischen Einsatz und die BFS aufgrund des bereits extensiven Einsatzes im deutschsprachigen Rau
Keywords: Bewegung; Gesundheit; Rehabilitation; Wohlbefinden; Messung

Disordered Eating and Exercise Dependence in Endurance Athletes - Zeulner, Bernd; Ziemainz, Heiko; Beyer, Christian; Hammon, Matthias; Janka, Rolf Matthias (Advances in Physical Education, 2016)
UnivIS-Import:2016-06-01:Pub.2016.phil.dps.iss.lsw.disord
Keywords: Exercise; Addiction; Dependence; Endurance; Athletes

Entwicklung eines Fragebogens zur Messung der kommunalen Kapazitäten für partizipative Bewegungsprogramme: eine Think-aloud-Studie - Till, Maike; Abu-Omar, Karim; Streber, Anna; Fleuren, Tobias; Herbert-Maul, Annika; Reimers, Anne Kerstin; Ziemainz, Heiko (Prävention und Gesundheitsförderung, 2023)
Background: Communities are of crucial importance for health promotion and the prevention of diseases. Local capacities are especially important for the successful implementation of health promotion projects and for reaching the target population. When considering the scale-up of projects with a focus on physical activity promotion (BIG and GESTALT) in the community setting, it is of great importance to develop a tool that can measure those capacities. Objectives: A questionnaire for the pragmatic measurement of capacities through local authorities was developed, tested, and revised within a think-aloud study. Methods: Based on empirical evidence, we developed a capacity questionnaire which was completed by six project coordinators during a think-aloud study. Data was analyzed using qualitative content analysis and the response-process-theory. Following the analysis, the questionnaire was adapted. Results: Participants mentioned a total of 81 errors in four categories, which had been adjusted: 1) comprehension, 2) retrieval, 3) judgement, 4) response. The final questionnaire comprises 63 questions in six areas: participation, local leadership, available resources, networking and cooperation, health care, and BIG-specific questions. Conclusion: The questionnaire provides physical activity promotion projects with the opportunity to pragmatically measure capacities in the community setting.
Created from Fastlane, Scopus look-up
Keywords: Capacity development; Community Development; Participation; Physical activity promotion

Evaluating physical activity interventions for socioeconomically disadvantaged adults through the RE-AIM framework: A systematic review of experimental and non–/quasi-experimental trials - Linder, Stephanie; Ferschl, Susanne; Abu-Omar, Karim; Ziemainz, Heiko; Reimers, Anne Kerstin (Preventive Medicine Reports, 2022)
The promotion of physical activity in people from lower social strata is a public health priority. Previous reviews of physical activity interventions among socioeconomically disadvantaged adults have focused on intervention effectiveness without considering their translation into practice. This review utilised the RE-AIM framework (Reach, Efficacy/Effectiveness, Adoption, Implementation, Maintenance) to (1) evaluate the extent to which experimental and non–/quasi-experimental trials of interventions to promote physical activity among socioeconomically disadvantaged adults report on issues of internal and external validity and (2) to provide recommendations for future intervention studies. Four databases were searched through June 2021. We included studies published in English or German since 2000 that tested physical activity interventions for socioeconomically disadvantaged adults. Two researchers coded all studies using a validated RE-AIM data extraction tool with 61 indicators referring to internal and external validity. Binary coding (yes = 1/no = 0) was applied to calculate the number and percentage of studies reporting each of the indicators. We included 39 studies of which 22 were non–/quasi-experimental trials. Indicators of reach were most frequently reported (59.2%), followed by implementation (38.9%) and efficacy/effectiveness (28.9%). Dimensions related to external validity were least frequently reported (adoption: 21.9%, maintenance: 17.8%). Few differences were found between experimental and non–/quasi-experimental trials. Analysis showed overall poor reporting of components related to internal and external validity. We recommend that future research should increase attention on reporting indicators of internal and external validity to facilitate their translation and implementation into real world settings. Trial registration: The review was registered with PROSPERO (CRD42021283688).
CRIS-Team Scopus Importer:2022-08-26
Keywords: External validity; Physical activity; RE-AIM; Socioeconomic disadvantage

Evaluation eines Aufmerksamkeitstrainings im Grundlagenbereich (abstract) - Lochmann, Matthias; Ziemainz, Heiko; Poimann, Dino (2016)
Keywords: Aufmerksamkeitstraining; Grundlagenbereich

Evaluation Mentalen Trainings im triathlonspezifischen Disziplinwechsel im Jugend- und Juniorenbereich - Ziemainz, Heiko; Stoll, Oliver; Adler, Katrin (Leistungssport, 2003)
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.evalua

Evaluation psychologischen Trainings im triathlonspezifischen Disziplinwechsel - Ziemainz, Heiko; Stoll, Oliver; Küster, Claudia; Alder, Katrin (15. Internationales Triathlonsymposium Bad Seegeberg 2002, 2002)
UnivIS-Import:2015-04-16:Pub.2002.phil.dps.iss.lsw.evalua

Evaluation psychologischen Trainings im Triathlonwechsel - Ziemainz, Heiko; Stoll, Oliver; Küster, Claudia; Adler, Katrin (BISp-Jahrbuch 2002, 2003)
UnivIS-Import:2015-04-20:Pub.2003.phil.dps.iss.lsw.evalua_9

Förderung kognitiver Lernprozesse durch bewegtes Lernen - Viehoff, Franziska; Ziemainz, Heiko (Sportpraxis, 2020)

“For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women - Sauter, Alexandra; Herbert-Maul, Annika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Frahsa, Annika; Linder, Stephanie; Herrmann-Johns, Anne (Frontiers in Public Health, 2022)
Introduction: Community-based participatory research (CBPR) is an effective health promotion approach for reaching socially disadvantaged groups. However, there is limited evidence on how such interventions and their effects can be reproduced across time and place. The present study examines the effects of BIG (i.e., movement as an investment in health), a long-standing German CBPR project. Since 2005, BIG has aimed to empower women in difficult life situations to increase control over their health determinants and reduce social inequalities by promoting physical activity. One of BIG's key features is its implementation in several German municipalities since 2005. This study explores (a) whether participation could change women's empowerment, and (b) how increased empowerment affects other areas of women's lives. Methods: With a total of 63 interviewees (i.e., 40 participating women, 7 trainers, 3 project coordinators, and 13 stakeholders), we conducted 53 semi-structured qualitative interviews in five BIG communities between 2007 and 2011. Some interviews were conducted with two people simultaneously. The interview guide contained questions on various dimensions of empowerment (e.g., project engagement, increased self-efficacy, and developed competencies). Framework analysis was used for the analytical process. Results: BIG contributed to women's empowerment in various ways, including increased self-efficacy, social network promotion, competency development, and increased motivation to change physical activity behavior. Women who took on added tasks and became more involved in project planning also strengthened their organizational empowerment. Furthermore, increased empowerment had a positive influence on the women's quality of life, family, and professional lives. Conclusion: The novel findings helped in understanding the effects of a complex empowerment-based approach that promoted physical activity among women in difficult life situations. Future research should focus on the long-term effects of these programs and their transferability to other sites. Further effort is necessary in the area of public health policy.
CRIS-Team Scopus Importer:2022-08-26
Keywords: community-based participatory research; empowerment; ethnic minority; health promotion; low socioeconomic status; physical activity; qualitative research; women's health

Gesundheitsbezogene Lebensqualität bei Arthrose der unteren Extremität - Messverfahren - Ziemainz, Heiko; Peters, Stefan (Bewegungstherapie und Gesundheitssport, 2010)

Handbuch der kommunalen Sportentwicklungsplanung - Rütten, Alfred; Ziemainz, Jana; Ziemainz, Heiko (Landessportbund Hessen, 2003)
UnivIS-Import:2019-03-21:Pub.2003.phil.dss.lsw.handbu

Handbuch der kommunalen Sportentwicklungsplanung - Rütten, Alfred; Ziemainz, Jana; Ziemainz, Heiko (Landessportbund Hessen, 2003)
UnivIS-Import:2015-04-02:Pub.2003.phil.dps.iss.lsw.handbu

Handlungskontrolle und Stressintervention im Triathlon - Ziemainz, Heiko (Meyer & Meyer, 1999)
UnivIS-Import:2015-04-02:Pub.1999.phil.dps.iss.lsw.handlu
Keywords: Stress; Handlungskontrolle; psychologisches Training; Triathlon

Hat gesundheitsorientiertes Muskeltraining positive Wirkungen auf psychische Gesundheit? - Ziemainz, Heiko; Herold, Andre; Müller, Ralf (Gesundheitssport und Sporttherapie, 2001)
UnivIS-Import:2015-03-09:Pub.2001.phil.dps.iss.lsw.hatges

Health perception influence on physical activity level between different age groups - Ciddio, Paola; Ziemainz, Heiko; Schena, Federico; Rütten, Alfred (Research to Action for an Aging Society, 2005)
UnivIS-Import:2015-03-09:Pub.2005.phil.dps.iss.lsw.health

International vergleichende Sportwissenschaft - Ziemainz, Heiko; Röger, Ulrike (Leipziger Sportwissenschaftliche Beiträge, 2006)
UnivIS-Import:2015-03-09:Pub.2006.phil.dps.iss.lsw.intern

Key performance indicators of cooperative planning processes: Case study results from German sport science and physical activity promotion projects - Sommer, Raluca; Linder, Stephanie; Ziemainz, Heiko; Gelius, Peter (German Journal of Exercise and Sport Research, 2021)
Objective: The aim of this study was to map the phases and individual steps of the cooperative planning process, a specific participatory approach frequently used in German sports and physical activity promotion, and to explore facilitators, barriers, and challenges experienced by those leading its implementation in selected projects. Background: More than half of the global population is not physically active enough. Therefore, the demand for more effective physical activity programs is growing. Participatory-based interventions, using the cooperative planning process, offer the potential to plan new programs that match population group and setting characteristics. This approach was extensively applied in German sports and physical activity fields, serving as a mechanism to develop and implement specific measures to change the population’s behaviour. We analysed four German empirical projects promoting sports and physical activity to identify how the approach was adapted to each project, which phases were considered, and which key performance indicators enhanced (facilitators), exacerbated (barriers), or challenged the process. Methods: This study used a mixed-methods approach, including a systematic analysis of documents (n = 10) and in-depth, semi-structured interviews (n = 4) with the empirical projects’ scientific members. Results: The cooperative planning process was shaped across its phases by several facilitators, challenges, and barriers. Diverse assessment procedures and recruitment tools can facilitate preparation of the process, while moderation requires particular attention during the development phase. Identifying a champion in the transition subphase and providing ongoing scientific counselling can assure the implementation of an action plan with tailored measures for sports and physical activity promotion. Conclusions: This study contributes to a better understanding of the complexity of the cooperative planning approach and, therefore, flexibility in sports and physical activity promotion projects. Many preparation actions, several challenges in the planning process, and a critical transition in implementation responsibilities should be considered by future projects intending to adopt the approach.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Collaborative models; Participatory approach; Participatory intervention method; Process evaluation; Qualitative research

Kommunale Bewegungsförderung für Frauen aus menschenrechtlicher Sicht - Sommer, Raluca; Till, Maike; Messing, Sven; Ziemainz, Heiko; Abu-Omar, Karim (Public Health Forum, 2024)
Der Globale Aktionsplan für Bewegung der Weltgesundheitsorganisation fordert die Anwendung eines menschenrechtsbasierten Ansatzes als Leitprinzip für Maßnahmen der Bewegungsförderung. Es ist bislang unklar, auf welche Art eine menschenrechtliche Perspektive in der Praxis der Bewegungsförderung sinnvoll angewendet werden kann. Dies wird am Beispiel des BIG-Projekts, einem Bewegungsangebot für Frauen im kommunalen Raum, diskutiert und anhand von menschenrechtlichen Kriterien analysier

Laufen in Gießen - Prochnow, Jürgen; Welz, Reiner; Ziemainz, Heiko (LAS, 1999)
UnivIS-Import:2015-04-02:Pub.1999.phil.dps.iss.lsw.laufen

Laufen psychotherapeutisch nutzen - Stoll, Oliver; Ziemainz, Heiko (Springer, 2012)
Breitensport für die Therapie nutzbar gemacht Joggen, Laufen und Walking scheinen eine hohe Akzeptanz zu haben. Inzwischen ist auch ihre therapeutische Wirksamkeit nachgewiesen. In diesem Buch werden neben Grundlagen auch die Besonderheiten in der Anwendung bei einzelnen Störungsbildern beschrieben. Außerdem wird solide auf Kontraindikationen und Grenzen hingewiesen. <br
UnivIS-Import:2019-03-21:Pub.2012.phil.dss.lsw.laufen
Keywords: Laufen; Therapie; Lauftherapie

Laufen psychotherapeutisch nutzen : Grundlagen, Praxis, Grenzen - Stoll, Olliver; Ziemainz, Heiko (Springer, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.iss.lsw.laufen
Keywords: Laufen; Therapie; Lauftherapie

Lauftherapie - Wirkungen und Perspektiven - Stoll, Oliver; Ziemainz, Heiko (UEFA Fussball Europameisterschaft 2012, 2012)

Lebenswelt, Sportunterricht und Gesundheit. Empirische Befunde zur Bedeutung alltäglicher Bewegungsräume für Kinder und Jugendliche - Rütten, Alfred; Ziemainz, Heiko (Sportunterricht, 2001)
UnivIS-Import:2015-03-09:Pub.2001.phil.dps.iss.lsw.lebens
Keywords: Empirische Untersuchung; Kind; Bewegungsraum; Gesundheit; Gesundheitsförderung; Bewegung Motorische; Sportpädagogik; Sportunterricht; Freizeitgestaltung; Alltag; Bedeutung; Jugendlicher

Measuring Subjective Well-Being in Exercise Interventions: Overview and Recommendations - Peters, Stefan; Ziemainz, Heiko (Asian Journal of Exercise and Sports Science, 2014)
There is a growing body of evidence that exercise has a positive influence on subjective well-being under certain circumstances. Actors in health sports should hence be able to investigate their actions regarding the influence on the well-being of the participants. The purpose of this narrative review is to give an overview of existing methods of measurement concerning subjective well-being and to publish recommendations for the practical application. The search was narrowed down to multidimensional questionnaires, measuring mainly the affective component of subjective well-being. Six instruments, (e.g., the Activation Deactivation Adjective Checklist [AD ACL], Profile of Mood States [POMS] and the Multiple Affect Adjective Checklist [MAACL-R]) are finally reviewed after an introduction that outlines the categories of well-being and reviews the mechanisms that have been suggested to explain the beneficial effects of exercise. The questionnaires vary sizably concerning their theoretical background, psychometric properties and structure. The suitability for various domains can be verified regarding these differences. The POMS for example can be recommended because of the international comparability, the PANAS because of the time-efficient use and the MAACL-R, because it covers many dimensions of affect.<br
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.lsw.measur

Mentale Fitness - eine unterschätzte Ressource - Ziemainz, Heiko (HR-Performance, 2012)

Mentale Trainingsformen im Langstreckenlauf - Stoll, Oliver; Ziemainz, Heiko (Afra, 2000)
UnivIS-Import:2015-04-02:Pub.2000.phil.dps.iss.lsw.mental
Keywords: Sportpsychologie; psychologisches Training; Langstreckenlauf

Mentale Trainingsformen im Schwimmen - Seufert, Katrin; Stoll, Oliver; Ziemainz, Heiko (Feldhaus Verlag, 2021)

Mentale Trainingsformen im Triathlon - Ziemainz, Heiko; Rentschler, Wolfgang (Afra, 2003)
UnivIS-Import:2015-04-02:Pub.2003.phil.dps.iss.lsw.mental

Mentale Trainingsformen im Triathlon - Ziemainz, Heiko; Rentschler, Wolfgang (Feldhaus Verlag, 2020)

Mentaltraining im Langstreckenlauf - Stoll, Oliver; Ziemainz, Heiko (Czwalina, 2009)

Mentaltraining im Triathlon - Ziemainz, Heiko; Rentschler, Wolfgang (Feldhaus, 2014)
Band 5 der Buchreihe Mentaltraining im Sport behandelt psychologische Trainingsformen, die in der Ausdauersportart Triathlon von besonderer Bedeutung sind. Dabei werden die wichtigsten triathlonspezifischen Probleme aufgegriffen (z. B. der triathlonspezifische Wechsel) und Lösungsmöglichkeiten vorgeschlagen. Der Bogen spannt sich von Technik- und Taktikschulung, über den Umgang mit belastenden Wettkampfsituationen und deren Bewältigung, über Aspekte der Motivierung bis zur Willensschulung. Die Autoren versuchen dabei grundlegende sportpsychologischen Erkenntnisse aber vor allem aktuelleForschungsergebnisse auf dem Gebiet der psychologischen Trainingsverfahren aufzubereiten, dass sie sowohl für den Athleten als auch für den Trainer leicht verständlich und an praktische Ziel- und Aufgabenstellungen im Training und Wettkampf orientiert sind. Kurz gesagt: Die Autoren haben versucht, komplexe psychologische Theorien bzw. Modelle in die Sprache der Sportler zu übersetzen und ihnen sportartspezifische Anleitungen zur Anwendung mentaler Trainingsformen an die Hand zu geben.<br
UnivIS-Import:2016-02-10:Pub.2014.phil.dps.iss.lsw.mental
Keywords: Mentaltraining; Triathlon; Sport

Objektive Messung technomotorischer Fertigkeiten mittels Funkortungstechnologie - Poimann, Dino; Ziemainz, Heiko; Lochmann, Matthias („Fußball 4.0 – Hightech in Training, Wettkampf und Ausbildung“ - Jahrestagung der dvs-Kommission Fußball, 2015)

Physical Activity Monitoring in Europe. The European Physical Activity Surveillance System (EUPASS). Approach and Indicator Testing - Rütten, Alfred; Vuillemin, Anne; Ooijendijk, WTM; Schena, Frederico; Sjöström, Michael; Stahl, Thomas; Vanden Auweele, Y; Welshman, J; Ziemainz, Heiko (Public Health Nutrition, 2003)
Objectives: The main objective of this paper is to describe the approach and specific findings of the European Physical Activity Surveillance System (EUPASS) research project. In particular, the analysis presented aims at testing the reliability, comparability and predictive power of different sets of physical activity (PA) indicators. Design: First, a panel study based on computer-aided telephone interview (CATI) was designed to report PA data of a representative, selected group of about 100 persons per country at three points in time. Second, a CATI time series survey was carried out with the goal of realising about 100 interviews per month over six consecutive months. Setting: The project was carried out in eight European countries to support the development of the European Union's (EU) Health Monitoring Programme. Subjects: Random population samples (subjects aged 18 years and older) were drawn from each participating country. Results: While many PA indicators used in EU countries to date as well as the psychosocial and environmental measures tested in the present study had acceptable to good reliability coefficients, the test-retest reliability scores of the International Physical Activity Questionnaire (IPAQ) version tested (the short (last 7 days) telephone interview IPAQ; IPAQ-S7T) were rather low. The comparability between extant national PA items and the IPAQ-S7T was low for all countries. The strongest predictors of perceived health were the psychosocial and environmental PA indicators. Conclusions: According to the results of the present study, more research is needed to further investigate and improve the quality of the IPAQ. In addition, the specific predictive power of the tested psychosocial and environmental PA indicators on perceived health should be of particular interest for designing health surveillance activities in the futur
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.physic
Keywords: Indicator testing; Monitoring; Physical activity; Public health

Physical inactivity in healthy, obese, and diabetic adults in Germany: An analysis of related socio-demographic variables - Linder, Stephanie; Abu-Omar, Karim; Geidl, Wolfgang; Messing, Sven; Sarshar, Mustafa; Reimers, Anne Kerstin; Ziemainz, Heiko (PLoS ONE, 2021)
Background Adults with diabetes or obesity are more likely to be physically inactive than healthy adults. Physical activity is essential in the management of both diseases, necessitating targeted interventions in these groups. This study analysed physical inactivity (defined as not taking part in leisure-time physical activity) in over 100,000 adults in Germany considering their body mass index and the presence of diabetes. Furthermore, the relationship between specific socio-demographic factors with physical inactivity was investigated, particularly focussing diabetic and obese people, to refine the identification of risk-groups for targeted interventions on physical activity promotion. Methods Data from 13 population-based health surveys conducted in Germany from 1997 to 2018 were used. The relevant variables extracted from these datasets were merged and employed in the analyses. We included data from 129,886 individuals in the BMI analyses and 58,311 individuals in the diabetes analyses. Logistic regression analyses were performed to identify the importance of six socio-demographic variables (age, sex/gender, education, income, employment, and migration) for the risk of physical inactivity. Results Obese and diabetic people reported a higher prevalence of physical inactivity than those who were not affected. Logistic regression analyses revealed advanced age, low education level, and low household income as risk factors for physical inactivity in all groups. A twosided migration background and unemployment also indicated a higher probability of physical inactivity. Conclusion Similar socio-demographic barriers appear to be important determinants of physical inactivity, regardless of BMI status or the presence of diabetes. However, physical activity promoting interventions in obese and diabetic adults should consider the specific disease-related characteristics of these groups. A special need for target group specific physical activity programmes in adults from ethnic minorities or of advanced age was further identified.<br

Präventionsfeld Triathlon - Ziemainz, Heiko; Fraunberger, Leonard (Gesundheitsrisiko Klimawandel - Neue Herausforderungen für Sport, Beruf und Alltag, 2024)
Keywords: Triathlon; Klima; Ausaduersport

Preferences of women in difficult life situations for a physical activity programme: protocol of a discrete choice experiment in the German NU-BIG project - Pedron, Sara; Herbert-Maul, Annika; Sauter, Alexandra; Linder, Stephanie; Sommer, Raluca; Vomhof, Markus; Gontscharuk, Veronika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Holle, Rolf; Laxy, Michael (BMJ Open, 2023)
Introduction The BIG project ('Bewegung als Investition in die Gesundheit', ie, 'Movement as Investment in Health') was developed in 2005 as a community-based participatory research programme to offer accessible opportunities for physical activity to women in difficult life situations. Since then, the programme has been expanded to eight sites in Germany. A systematic evaluation of BIG is currently being conducted. As part of this effort, we strive to understand the preferences of participating women for different aspects of the programme, and to analyse their willingness to pay. Methods and analysis In this protocol, we describe the development and analysis plan of a discrete choice experiment (DCE) to investigate participants' preferences for a physical activity programme for women in difficult life situations. The experiment will be embedded in a questionnaire covering several aspects of participation in the programme (eg, reach, efficacy and further effects) and the socioeconomic characteristics of all active participants. After a thorough search of the literature, BIG documents review and expert interviews, we identified five important attributes of the programme: course times, travel time to the course venue, additional social activities organised by BIG, consideration of wishes and interests for the further planning of courses and costs per course unit. Thereafter, we piloted the experiment with a sample of participants from the target group. After data collection, the experiment will be analysed using a conditional logit model and a latent class analysis to assess eventual heterogeneity in preferences. Ethics and dissemination Understanding women's preferences will provide useful insights for the further development of the programme and ultimately increase participation and retention. The questionnaire, the included DCE and the pretest on participants received ethical approval (application no. 20-247-1-B). We plan to disseminate the results of the DCE in peer-reviewed journals, national conferences and among participants and programme coordinators and organisers.
CRIS-Team Scopus Importer:2023-07-28
Keywords: HEALTH ECONOMICS; SOCIAL MEDICINE; SPORTS MEDICINE

Promoting physical activity among socially disadvantaged women: Findings on target group outreach, course retention, and impact of the BIG project as a case study for participatory interventions in community settings Bewegungsförderung bei sozial benachteiligten Frauen: Erkenntnisse zur Zielgruppenerreichung, Kursbindung und Wirkung des BIG-Projekts als Fallstudie für partizipative Interventionen im kommunalen Setting - Linder, Stephanie; Herbert-Maul, Annika; Ziemainz, Heiko; Thiel, Ansgar; Holle, Rolf; Laxy, Michael; Pedron, Sara; Abu-Omar, Karim (German Journal of Exercise and Sport Research, 2023)
Background: The BIG project—a participatory project in a community setting (“Bewegung als Investition in Gesundheit”)—was developed in 2005 to facilitate access to physical activity for disadvantaged women. Since then, BIG has been transferred to 17 municipalities. Aim: To investigate whether socially disadvantaged women can be reached and retained in exercise classes in the BIG project. In addition, the information provided by the women on their state of health and exercise is reported. Finally, we will examine whether five risk factors associated with social disadvantages are associated with health status and physical activity. Methods: Quantitative cross-sectional data from six survey waves (2006–2013) from two project sites (Erlangen, Regensburg) were summarized. To analyze the reach of the target group, participant characteristics (N = 430) were compared with population data from the sites. The reach of the target group, course retention, and data on health status and physical activity were also descriptively analyzed. The influence of risk factors and physical activity on health status was examined by multivariate regression analyses. Results: Of the participants, 67% had at least one risk factor. Women participated in the BIG courses for a mean of 2.4 years. Over 50% of women reported improved health, and over 60% exercised more compared with before BIG. The number of risk factors present was associated with the health status compared to the time before BIG (p < 0.001). Lack of German language skills showed a significant association with current health status. Conclusions: The BIG project reaches socially disadvantaged women. In particular, women with few risk factors report positive change in health status and physical activity compared to the time before BIG participation. Here, the number of risk factors present and lack of German language skills seem to be important.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Health promotion; Participation; Physical activity promotion; Socioeconomic disparities in health; Target group reach

Psychologie in Ausdauersportarten - Ziemainz, Heiko; Schmidt, Ulf; Stoll, Oliver (Afra, 2000)
UnivIS-Import:2015-04-02:Pub.2000.phil.dps.iss.lsw.psycho
Keywords: Sportpsychologie; Ausdauersport; Lauftherapie; Sportsucht; Stress; Persönlichkeit; Motivation

Psychologisches Training in Ausdauersportarten - Sinn oder Unsinn - Ziemainz, Heiko; Stoll, Oliver (Ausdauer und Ausdauertraining, 2007)
UnivIS-Import:2019-03-21:Pub.2007.phil.dss.lsw.psycho
Keywords: Psychologisches Training; Ausdauer; Ausdauertraining; Sportpsychologie

Psychologisches Training in Ausdauersportarten - Sinn oder Unsinn - Ziemainz, Heiko; Stoll, Oliver (Ausdauer und Ausdauertraining, 2007)
UnivIS-Import:2015-04-16:Pub.2007.phil.dps.iss.lsw.psycho
Keywords: Psychologisches Training; Ausdauer; Ausdauertraining; Sportpsychologie

Qualitätsgesichertes System der Talentsichtung, -auswahl und -förderung - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (Sport und Buch Strauss, 2005)
UnivIS-Import:2015-04-02:Pub.2005.phil.dps.iss.lsw.qualit_28

Qualitätsgesichertes System der Talentsuche und -auswahl - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (Strauß, 2005)
UnivIS-Import:2015-04-20:Pub.2005.phil.dps.iss.lsw.qualit_9

Qualitätsgesichertes System der Talentsuche und -auswahl - Theoretischer Ansatz, Methode, erste Ergebnisse - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (Beiträge zum Nachwuchsleistungssport, 2005)
UnivIS-Import:2015-04-20:Pub.2005.phil.dps.iss.lsw.qualit

Qualitätsmanagement im Seniorensport. Mögliche Ansätze, Methoden und Resultate am Beispiel kommunaler Bewegungsinfrastruktur - Ziemainz, Heiko (Perspektiven bewegten Alterns, 2002)
UnivIS-Import:2015-04-20:Pub.2002.phil.dps.iss.lsw.qualit_8

Quality Management in Talent Identification, Talent Selection, and Talent Development - Rütten, Alfred; Ziemainz, Heiko; et al. (Talentidentification, -selection and -development - problems and perspectives, 2004)
UnivIS-Import:2019-03-21:Pub.2004.phil.dss.lsw.qualit

Quality Management in Talent Identification, Talent Selection, and Talent Development - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (Talentidentification, -selection and -development – Problems and Perspectives, 2004)
UnivIS-Import:2015-04-16:Pub.2004.phil.dps.iss.lsw.qualit

Quality Management in Talent Identification, Talent Selection, and Talent Development - Initial Results - Röger, Ulrike; Ziemainz, Heiko; Rütten, Alfred (Talentidentification, -selection and -development – Problems and Perspectives, 2004)
UnivIS-Import:2015-04-16:Pub.2004.phil.dps.iss.lsw.qualit_9

Quality Management in Talent Identification, Talent Selection, and Talent Development - Initial Results - Ziemainz, Heiko; Rütten, Alfred; et al. (Talentidentification, -selection and -development - problems and perspectives, 2004)
UnivIS-Import:2019-03-21:Pub.2004.phil.dss.lsw.qualit_6

Quality of talent development systems: results from an international study - Röger, Ulrike; Rütten, Alfred; Ziemainz, Heiko; Hill, Randy (European journal for sport and society, 2010)
In this study a purpose-built framework for specifying quality criteria – structure, process and outcome – in talent development systems was developed and evaluated in an explorative international study. A standardized survey was conducted with 1020 survey participants from four nations (Australia, China, Germany and the USA) and four sports disciplines (athletics, gymnastics, swimming and volleyball). The overall response rate was 56.4%. The principal component analysis confirmed three out of the four determinants of the quality dimension structure (goals, resources, and opportunities). They were based on five to eleven items with a minimum factor loading of .51. For each of the dimensions process and outcome one factor with a minimum factor loading between .59 and .65 could be statistically confirmed. These findings suggest that the chosen conceptual framework is applicable for specifying quality criteria of talent development systems in different nations and sports. It can be used in further studies comparing the quality of sports systems between different nations and might be useful to develop a quality management approach for elite sport.
Keywords: quality assurance; quality management

Residential area, physical education, and the health of school aged children - Rütten, Alfred; Ziemainz, Heiko; Abu-Omar, Karim; Groth, Nicole (Health Education, 2003)
Explores the relationships between the perceived quality of physical education lessons, the perceived quality of opportunities for physical activity in a residential area, and the physical fitness and health of pupils attending Grades 5 and 9 in Germany. The data were collected from 300 pupils in a community in Saxony, using a standardized questionnaire and a standard test of sporting ability. Results indicated that girls evaluated the opportunities for physical activity in the residential area more critically than boys. Multivariate analysis showed that the subjective health status of pupils was associated with good physical fitness and a good perception of opportunities for physical activity in the residential area, but not with the perceived quality of physical education lessons. These results provide evidence that a relationship between the urban environment and physic
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.reside
Keywords: Exercise; Education; Residential areas; Urban areas; Health education; Pupils; Germany

Scaling Up Physical Activity Promotion Projects on the Community Level for Women in Difficult Life Situations and Older People: BIG-5 and GET-10—A Study Protocol - Till, Maike; Abu-Omar, Karim; Herbert-Maul, Annika; Fleuren, Tobias; Reimers, Anne Kerstin; Ziemainz, Heiko (Frontiers in Public Health, 2022)
Introduction: Physical inactivity is a major risk factor for a population's health, especially among socially disadvantaged groups. Many health promotion projects focus on increasing physical activity among their respective target groups. However, because they are mostly developed and implemented under laboratory conditions, they fail when being scaled to real-world settings. The community-based participatory research projects BIG and GESTALT have demonstrated their effectiveness regarding the physical activity promotion in real-world settings by employing a participatory method. Material and Analysis: Within the context of the BIG-5 and GET-10 projects, these previously implemented and tested participatory projects are scaled to 15 additional settings in Bavaria, Germany. By applying an overarching mixed-methods evaluation framework, the aim is to gain insights into a) the recruitment of communities for scale-up; b) the specific results of the projects according to the RE-AIM framework. In the recruitment of communities, standardized information on the first contact, the consultation process, the person in charge, and previously implemented health promotion projects are collected. A systematic web search will complete information on each community and their health promotion activities. Results will be compared with information on those communities most in need, here according to the deprivation index of communities in Bavaria, Germany. The scale-up process and its results will be measured using semi-structured interviews with project coordinators. A standardized questionnaire will be used with the course's participants. Applying the RE-AIM framework, the collected data will be analyzed deductively. Discussion: We expect the results to be highly relevant for the effective scale-up of any health promotion project. The study will enhance the understanding of how to reach those communities most in need of health promotion projects and will identify the barriers coordinators face in reaching socially disadvantaged groups. Conclusion: Although participatory projects are often used as individual projects, little is known about the scaling up of participatory health promotion projects. This cross-cutting evaluation of two projects aims at producing data on the barriers and facilitators for the reach of settings most in need, and those success factors for a durable implementatio
Keywords: scale-up; socially disadvantaged; physical activity; community-based participatory research; low socioeconomic status; ethnic minoritie; vulnerable groups

Sportpsychologie im Kinder- und Jugendfußball - Ziemainz, Heiko; Drescher, Amely; Ritter, Daniel; Poimann, Dino; Lochmann, Matthias (Spitta Verlag GmbH & Co. KG, 2016)
Keywords: Sportpsychologie; Kinderfußball; Jugendfußball; Fußball

Sportpsychologie in der Praxis am Beispiel der Betreuung von Landes- und BundeskaderathletInnen - Ziemainz, Heiko (23. Internationales Triathlon-Symposium Erding 2008, 2009)

Sportpsychologie in der Praxis des Leistungssports am Beispiel der Betreuung von Landes- und Bundeskaderathleten der Deutschen Triathlon Union - Ziemainz, Heiko; Stoll, Oliver (Handbuch sportpsychologischer Praxis, 2012)

Sportpsychologische Betreuungsmaßnahme im Triathlon - Ziemainz, Heiko; Rasche, Friederike (Sportpsychologische Betreuung des deutschen Olympiateams 2004, 2005)
UnivIS-Import:2015-04-20:Pub.2005.phil.dps.iss.lsw.sportp

Sportstätten - Rütten, Alfred; Ziemainz, Jana; Ziemainz, Heiko (Themenfelder der Sportwissenschaft, 2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dps.iss.lsw.sports

Sportstätten-Management - Bach, Lüder; Ziemainz, Heiko; Delp, Horst; Kupper-Heilmann, Susanne (Landessportbund Hessen, 2004)
UnivIS-Import:2015-04-02:Pub.2004.phil.dps.iss.lsw.sports

Sportstättenmanagement - Ziemainz, Heiko (Handbuch Sport und Technik, 2001)
UnivIS-Import:2015-04-20:Pub.2001.phil.dps.iss.lsw.sports
Keywords: Sportstätten; Sportstättenmanagement

Sportsucht und pathologisches Bewegungsverhalten - Kleinert, Jens; Zeeck, Almut; Ziemainz, Heiko (Kohlhammer, 2020)
Das Buch beschreibt den aktuellen Stand zum Thema Sportsucht, darunter Definitionen, Prävalenz, Entstehungsbedingungen, Diagnostik und Therapie. Es behandelt sowohl das Auftreten von Sportsucht in spezifischen Bereichen wie Ausdauersport und Fitnesssport als auch die Zusammenhänge mit anderen Störungsbildern wie etwa Essstörungen oder Muskeldysmorphie. Neben Entstehungsmodellen werden psychische und psychopathologische Hintergründe, diagnostische Möglichkeiten (z. B. Fragebögen) sowie präventive und therapeutische Ansätze ausgeführt.<br
Keywords: Sportsucht; Bewegung; Bewegungsverhalten

Sportunterricht und (sportbezogene) Selbstwirksamkeit. Erste empirische Befunde einer explorativen Feldstudie - Ziemainz, Heiko; Wagner, Petra; Rütten, Alfred (Leipziger Sportwissenschaftliche Beiträge, 2001)
UnivIS-Import:2015-03-09:Pub.2001.phil.dps.iss.lsw.sportb

Streßbewältigung und sportlicher Erfolg im Triathlon - Ziemainz, Heiko (Tectum, 1997)
UnivIS-Import:2015-04-02:Pub.1997.phil.dps.iss.lsw.strebe

Streßintervention im Triathlon - Ziemainz, Heiko; Stoll, Olliver (Leistungssport, 1998)
UnivIS-Import:2015-03-05:Pub.1998.phil.dps.iss.lsw.strein

Stress und Stressbewältigung im Biathlon - Adler, Katrin; Ziemainz, Heiko (Leistungssport, 2005)
UnivIS-Import:2015-03-09:Pub.2005.phil.dps.iss.lsw.stress

Stress und Stressbewältigung im Leistungssport - Stoll, Olliver; Ziemainz, Heiko (Sportwissenschaft, 2003)
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.stress

Talentauswahl, -suche und -förderung am Beispiel des australischen TALENT SEARCH-Programm - Ziemainz, Heiko; Gulbin, Jason; et al. (Leistungssport, 2001)

Talent Identification, Selection, and Development - Problems and Perspectives - Rütten, Alfred; Ziemainz, Heiko; Röger, Ulrike (Afra, 2004)
UnivIS-Import:2015-07-08:Pub.2004.phil.dps.iss.lsw.talent

Talent Identification, Selection, and Development - Problems and Perspectives - Ziemainz, Heiko; Rütten, Alfred; et al. (Afra, 2004)
UnivIS-Import:2019-03-21:Pub.2004.phil.dss.lsw.talent

Talent Identification, Talent Selection and Talent Development - The Example of the Australian TALENT SEARCH program - Ziemainz, Heiko; et al. (Talentidentification, -selection and -development - problems and perspectives, 2004)
UnivIS-Import:2019-03-21:Pub.2004.phil.dss.lsw.talent_5

Talent Identification, Talent Selection and Talent Development - The Example of the Australian TALENT SEARCH program - Ziemainz, Heiko; Hill, Randy (Talent Identification, Selection and Development - Problems and Perspectives, 2004)
UnivIS-Import:2015-04-16:Pub.2004.phil.dps.iss.lsw.talent_0

Talent selection, -identification and development exemplified in the Australian Talent Search Programme - Ziemainz, Heiko; Gulbin, Jason (New Studies in Athletics, 2002)
UnivIS-Import:2015-03-09:Pub.2002.phil.dps.iss.lsw.talent

The application of mental training in the rehabilitation of stroke patients - Review and calculating effect sizes - Ziemainz, Heiko; Hendrich, Simon Klaus; Schleinkofer, Michael; Pfeifer, Klaus (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2008)
In the rehabilitation of stroke patients, mental training is increasingly attracting attention as a promising psychological complement of common exercise therapy approaches [1,2]. This article aims at an analytical description of the empirical medical evidence and at the identification and assessment of the effects of mental training in the rehabilitation of stroke patients by calculating effect sizes. First of all in a systematic literature review all studies should be identified that applied mental training as an intervention for the rehabilitation of adult stroke patients. In total, 49 studies were identified and then classified based on their quality [3]. Of these, five were either randomized (4) or clinical (1) controlled studies, which formed the basis for calculating effect sizes [4]. The analysis yielded medium (ES >0.5) to high (ES >0.8) effect sizes [5]. Given these results, it seems advisable to apply mental training as a (additional) treatment in the rehabilitation of stroke patients. © Georg Thieme Verlag KG Stuttgar
Keywords: Hemiplegia; Mental practice; Mental training; Motor imagery; Rehabilitation; Stroke

The Application of Psychological Assessment Methods in Sport Psychology in Germany - Ziemainz, Heiko; Neumann, Gabriele; Rasche, Friederike; Gelius, Peter; Stemmler, Mark (Sport science review, 2009)

The long-term public health impact of a community-based participatory research project for health promotion among socially disadvantaged women—a case study protocol - Abu-Omar, Karim; Ziemainz, Heiko; Loss, Julika; Laxy, Michael; Holle, Rolf; Thiel, Ansgar; Herbert-Maul, Annika; Sauter, Alexandra; Linder, Stephanie; Till, Maike (Frontiers in Public Health, 2021)
Introduction: Community-based participatory research (CBPR) is considered to be of high potential for health promotion among socially disadvantaged groups. However, the long-term implementation and transfer of these approaches remain challenging, and the public health impact they achieve is difficult to study. This also pertains to the potential health effects and cost-effectiveness of CBPR. This study protocol describes the follow-up case study (NU-BIG) after 15 years of the BIG project (“movement as investment in health”), a project to promote physical activity among socially disadvantaged women. Through a participatory approach BIG empowers the adressed women to plan and implement low-thresholf physical activity offers. Since the project started in 2005 it was transferred to 17 communities in Germany. Materials and Analysis: NU-BIG intends to examine the long-term effects, including economic aspects, of the BIG project on individual and structural levels at all project sites as well as it’s long-term implementation and transfer. NU-BIG is a cross-sectional and longitudinal study using a mixed method approach. For the longitudinal section, we re-analyse existing data from former BIG evaluations. For cross-sectional data collection we use questionnaires and conduct qualitative interviews and focus groups. Women who take part in BIG programme offers are part of the research team and will use the photo-voice approach to report on the effects of BIG. The study population consists of about 800 women who participate in BIG project offers and 50 persons involved in the implementation of the BIG project at local sites. Discussion: The expected results from NU-BIG are highly relevant for studying the long-term public health impact of CBPR. In particular, this project intends to answer questions on how the transfer of such projects can succeed and which factors determine if a CBPR project can be sustained at the community level. Eventually these results can contribute to the further development of participatory approaches to provide effective health promotion among socially disadvantaged groups.<br
Keywords: long-term public health impact; physical activity; Community-Based Participatory Research; low socioeconomic status; Ethnic Minorities; Vulnerable groups

Towards a European Health Monitoring System. Results of a Pilot Study on Physical Activity - Rütten, Alfred; Rzewnicki, Randall; Ziemainz, Heiko; Ooijendijk, WTM; Schena, Frederico; Stahl, Timo; Vanden Auweele, Y; Welshman, J (Global Behavioral Risk Factor Surveillance, 2003)
UnivIS-Import:2015-04-20:Pub.2003.phil.dps.iss.lsw.toward

Trendsport - Neue Wege im Schulsport - Schuster, Matthias; Ziemainz, Heiko (Sportpraxis, 2009)

Triathlon in der (Grund-) Schule. Argumente für eine spielerische Einführung vonTriathlon in der (Grund-) Schule - Wirth, Christina; Ziemainz, Heiko (Triathlon für Kinder : Radfahren, Schwimmen und Laufen in Schule und Verein, 2013)

Triathlon in der Schule - Die Triathlonwechsel einführen und spielerisch vermitteln - Wirth, Christina; Ziemainz, Heiko (Triathlon für Kinder : Radfahren, Schwimmen und Laufen in Schule und Verein, 2013)

Triathlon: Lehrplankonform im Schulunterricht - Teil 1 - Vogel, Franz; Wirth, Christina; Ziemainz, Heiko (Sportpraxis, 2014)
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.lsw.triath

Using Different Physical Activity Measurements in Eight European Countries. Results of the European Physical Activity Surveillance System (EUPASS) Time Series Survey. - Rütten, Alfred; Ziemainz, Heiko; Schena, Frederico; Stahl, Timo; Stiggelbout, M; Vanden Auweele, Y; Vuillemin, Anne; Welshman, J (Public Health Nutrition, 2003)
Objectives: The European Physical Activity Surveillance System (EUPASS) research project compared several physical activity (PA) measures (including the International Physical Activity Questionnaire (IPAQ)) in a time series survey in eight countries of the European Union. The present paper describes first results provided by the different instruments regarding PA participation, frequency and duration, both at the European and national levels. The purpose of the present study is to explore and compare the specific quality and usefulness of different indicators rather than to provide valid and reliable prevalence data. Thus, the main focus is on discussion of the methodological implications of the results presented. Methods: A time series survey based on computer-aided telephone interviewing (CATI) was carried out in eight European countries over a six-month period. The study provided for about 100 realised interviews per month in each country (i.e. ∼600 per country). Descriptive statistical analysis was used to: (1) report IPAQ results on vigorous, moderate and light PA and sitting, as well as on the overall measure of calories expenditure (MET min-1), in the different countries; (2) compare these results with national PA indicators tested in EUPASS; and (3) compare IPAQ results with other European studies. Results: First, the scores for the different PA categories as well as for the overall measure of calories expenditure provided by the IPAQ appeared rather high compared with previous studies and public health recommendations. Second, the different PA measurements used in EUPASS provided completely different results. For example, national indicators used in Germany and The Netherlands to date neither corresponded in absolute values (e.g. means of PA or sitting) nor correlated with the IPAQ in any significant way. Third, comparing EU countries, the ranking for vigorous, moderate and light activities by use of the IPAQ differed from that of other European studies. For example, in the present analysis, German respondents generally showed higher scores for PA than the Finns and the Dutch, while, in contrast, findings from other studies ranked Finland before The Netherlands and Germany. Conclusions: The present analysis highlights some methodological implications of the IPAQ instrument. Among other things, differences in overall scores for PA as well as in the ranking of nations between the present results using IPAQ and other measures and studies may partly be due to the concepts of PA behind the measurements. Further analysis should investigate if the range of PA-related categories provided by the IPAQ is fully appropriate to measure all relevant daily activities; it may also consider the public health implications of mixing up different contexts of PA (e.g. work, leisure-time, transportation) in the IPAQ short versio
UnivIS-Import:2015-03-09:Pub.2003.phil.dps.iss.lsw.usingd
Keywords: International comparison; Measurement; Physical activity; Public health

Zum Einsatz sportpsychologischer Diagnostik in der Praxis des Leistungssports - Ziemainz, Heiko; Neumann, Gabriele; Rasche, Friederike; Stemmler, Mark Kurt (Zeitschrift für Sportpsychologie, 2006)
In der vorliegenden Arbeit erfolgt eine Bestandsaufnahme über Anwendung von und Bedarf an sport- psychologischer Diagnostik der in der Praxis des deutschen Spitzensports arbeitenden Sportpsychologen. Die Stichprobe rekrutierte sich aus den in der BISp-Sportpsychologie-Expertendatenbank (www.bisp-sportpsychologie.de) gelisteten Personen. Die Datenerhebung erfolgte mittels computergestützter Telefoninterviews. Durchschnittlich arbeiten die Sportpsychologen mit 20 Sportlern und 6 Trainern. Fast 88% der Sportpsychologen setzen in ihrer Arbeit mit Athleten Diagnostik ein. Alle Sportpsychologen, die Diagnostik durchführen, greifen auf die Explorationstechnik zurück. Zusätzlich werden standardisierte allgemeinpsychologische (75.0%), standardisierte sportspezifische (87.5%) und selbst entwickelte (71.9%) Testverfahren verwendet. Ein Großteil der Befragten berichtete u.a. über einen Bedarf an sport(art)spezifischen Verfahre
UnivIS-Import:2015-03-09:Pub.2006.phil.dps.iss.lsw.zumein
Keywords: Psychodiagnostik; Berufspraxis; angewandte Sportpsychologie; Spitzensport